ANALISIS KEUNGGULAN KOMPARATIF USAHA TANI LADA HITAM DI LAMPUNG DAN LADA PUTIH DI KALIMANTAN BARAT - YUHONO, J. T.; MAULUDI, LUDI (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
The comparative advantage analysis of black pepper in farm Lampung and white pepper's farm in West Kalimantan Study of the comparative advantage of pepper farm was conducted in Lampung as black pepper production centre with non-intensive pattern, and West Kalimantan as white pepper production centre with semi- intensive pattern fom January to March 1996. The objectives of this research were to analyze the comparative advantage of pepper farm from in terms of its capability to earn foreign exchange. Data wee conducted by survey method. Location was selected by purposive sampling method based on pepper farm pattern anner sampling was conducted by simple random sampling for each villages. The data were analyzed by using net social proitability and domestic esources cost. The result showed that pepper farm for both of production centre had comparative advantage to earn foreign exchange and the comparative advantage for semi intensive pattern was higher than that of non intensive patten. For the development of pepper in Indonesia the semi intensive pattern is better the non intensive pattern, there for it should be sugested.